Update on outpatient antibiotic prescribing during the COVID-19 pandemic: United States, 2020-2022 - Destani Bizune; Katryna Gouin; Lauren Powell; Adam L. Hersh; Lauri A. Hicks; Sarah Kabbani (Cambridge University Press, 2024)
We updated a descriptive analysis of national outpatient antibiotic prescribing during the COVID-19 pandemic. Prescribing volume was lower during 2020 and January-June in 2021 and 2022 compared to corresponding baseline months in 2019. Prescribing approached or exceeded baseline during July-December of 2021 and 2022 for all antibiotics, especially for azithromycin.